2021
DOI: 10.1016/j.jot.2021.10.009
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB activation impedes the transdifferentiation of hypertrophic chondrocytes at the growth plate of mouse embryos in diabetic pregnancy

Abstract: Background Diabetes mellitus could cause numerous complications and health problems including abnormality of endochondral bone formation during embryogenesis. However, the underlying mechanisms still remain obscure. Methods Streptozotoci (STZ) was injected to induce pregestational diabetes mellitus (PGDM) mouse model. The femurs of E18.5 mouse embryos from control and PGDM groups were harvested. Morphological staining was implemented to determine the abnormality of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Our results showed that ABA inhibited the nuclear translocation of P65 was consistent with the results of previous studies. They also confirmed that P65 is recruited to the BMP2 and Runx2 promoter and directs osteogenic programming in VICs 35 , 36 . However, ABA failed to reduce calcium deposition in already calcified im-hVICs ( Figure S3 ).…”
Section: Discussionmentioning
confidence: 58%
“…Our results showed that ABA inhibited the nuclear translocation of P65 was consistent with the results of previous studies. They also confirmed that P65 is recruited to the BMP2 and Runx2 promoter and directs osteogenic programming in VICs 35 , 36 . However, ABA failed to reduce calcium deposition in already calcified im-hVICs ( Figure S3 ).…”
Section: Discussionmentioning
confidence: 58%
“…Glycogen staining was performed using a Periodic Acid-Schiff (PAS) kit (Sigma-Aldrich) following the manufacturer's protocol. Immunofluorescence and immunohistochemical staining were performed as previously described [ 32 ]. Human or rat tissues were serially sectioned at thicknesses of 4 μm.…”
Section: Methodsmentioning
confidence: 99%